The Application of Jigsaw and Mind Mapping to Increase Student’s Learning Result - Fatmawati, Sri Endang (Unversitas Negeri Malang, 2018)
This research established from the case application of the studying model full of speech problem to the result of student and its happen before the existence of LCD facilities in the school. A solution to this case are studying model include jigsaw and mind mapping. This research is kind of research which changes the activity in the class and located in MA Al-Munawaroh Kembangbahu Lamongan to the 10th-grade social student. Data collection technic through question paper, observation paper, scoring format, notes from field research, documentation, and other questionnaire paper. The result of this research shows that there’s increasing the cognitive domain of the studying technic which by all student from the cycle 1 to cycle 2 are about 23%, affective domain this one 14,6% and psychomotor are 13 %.